2008
DOI: 10.1016/j.jtcvs.2008.03.071
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study of human factors, adverse events, and patient outcomes in surgery for pediatric cardiac disease

Abstract: Pediatric cardiac surgery is an ideal model to study the coordinated efforts of team members in a complex organizational structure. Adverse events occurred routinely during pediatric cardiac surgery and were mostly compensated. Case complexity was a significant predictor of major adverse events. The number of major adverse events per patient correlated with clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 27 publications
(48 reference statements)
2
96
0
1
Order By: Relevance
“…ElBardissi et al [27] collected and classified surgical errors and flow disruptions and concluded that improving communication would benefit cardiac surgery. Barach et al [34] explored the impact of adverse events in pediatric cardiac procedures and found communication problems as the most common category among minor events (those not expected to cause serious consequences or break in surgical flow). Hu et al [35] identified and classified process deviations (delays and safety compromises) during surgical procedures.…”
Section: Team Interactions Research In Surgerymentioning
confidence: 99%
“…ElBardissi et al [27] collected and classified surgical errors and flow disruptions and concluded that improving communication would benefit cardiac surgery. Barach et al [34] explored the impact of adverse events in pediatric cardiac procedures and found communication problems as the most common category among minor events (those not expected to cause serious consequences or break in surgical flow). Hu et al [35] identified and classified process deviations (delays and safety compromises) during surgical procedures.…”
Section: Team Interactions Research In Surgerymentioning
confidence: 99%
“…The non-routine events observed were afterwards validated by these medical professional as medical professionals provide context, valuation, relevance and clarity to a human factors partner 36. Although we acknowledge that not all non-routine events are task-related, it is critical to obtain a complete overview of all process variations, as these events could accumulate and add up to form a major event 6 9…”
Section: Methodsmentioning
confidence: 96%
“…Two observers performed real-time prospective observations of the PCS team from the inception of anaesthesia to the patient handover in the intensive care unit 14. The study included detailed process mapping, a comprehensive cognitive task analysis, detailing of the PCS team15 and training the observers in a validated and reliable manner all described elsewhere 6. Full institutional review board approval was attained.…”
Section: Methodsmentioning
confidence: 99%
“…In an observational study involving 102 pediatric cardiac surgical cases, an average of 16 adverse events were reported per patient, 30% occurring shortly after coming off CPB and most of them being related to communication and coordination failure. [13] Cognitive adjustment was the compensatory intervention in most of these nearmisses emphasizing the importance of qualification, training, and expertise. Another study from the Mayo clinic highlighted a strong correlation between the occurrence of technical error and teamwork disruption resulting from insufficient procedural information and poor communication/coordination between the surgeon, the anesthesiologist, and the perfusionist.…”
Section: Organizational Aspects and Human Factorsmentioning
confidence: 99%